Experimental investigation of µ-abrasive jet machining with dust collection mechanism. (2022) - Joy, Anoop; Paul, Lijo; Pradeep, P.V.
Abstract: Micro abrasive jet machining process is an advanced machining process used for the production of micro holes, micro channels and machining of different type of brittle materials. It is a non contact type machining process, were highly pressurized air and abrasive particles are mixed using a mixing chamber and directed towards the work piece. The material is removed by means of mechanical erosion. During the machining time, there are lot of abrasive particles expelled out and it may cause environmental pollution. To avoid this problem an abrasive dust collector mechanism with liquid film is used in the current work. In this experiment the work piece is placed in the liquid chamber and three input process parameters such as mass flow rate, standoff distance, motor speed and there effects on the output responses such as material removal rate, radial overcut and area of frosted zone is discussed. The process parameters are optimized using Taguchi method and utility concept in Minitab statistical software.